2009
DOI: 10.4269/ajtmh.2009.09-0114
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of BioUD to Other Commercially Available Arthropod Repellents against the Ticks Amblyomma americanum and Dermacentor variabilis on Cotton Cloth

Abstract: Abstract. BioUD is an arthropod repellent that contains the active ingredient 2-undecanone originally derived from wild tomato plants. Repellency of BioUD was compared with five commercially available arthropod repellents against the ticks Amblyomma americanum (L.) and Dermacentor variabilis Say in two-choice bioassays on treated versus untreated cotton cheesecloth. Overall mean percentage repellency against both species was greatest for and did not differ significantly between BioUD (7.75% 2-undecanone) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…Against mosquitoes under field conditions, BioUD on human skin provided the same repellency or was more efficacious than 25% and 30% DEET for 6 h in North Carolina, U.S.A. and Ontario, Canada, respectively (Witting- Bissinger et al, 2008). BioUD was also found to be more effective on cloth than many of the current commercial repellents for tick control (Bissinger et al, 2009b).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Against mosquitoes under field conditions, BioUD on human skin provided the same repellency or was more efficacious than 25% and 30% DEET for 6 h in North Carolina, U.S.A. and Ontario, Canada, respectively (Witting- Bissinger et al, 2008). BioUD was also found to be more effective on cloth than many of the current commercial repellents for tick control (Bissinger et al, 2009b).…”
Section: Introductionmentioning
confidence: 85%
“…Bioassays were conducted to determine repellency and the duration of repellent activity on filter paper or cotton cheesecloth using our standard two-choice bioassay (Witting- Bissinger et al, 2008;Bissinger et al, 2009aBissinger et al, , 2009b. On each tested surface, ticks were provided with a choice between the test compound (either 2-tridecanone or 2-undecanone) vs. the ethanol control.…”
Section: Two-choice Bioassaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Products with 20%-30% DEET are considered optimal for protection against most tick species (321), and concentrations >50% do not confer additional protection (320). IR3535 (3-[N-Butyl-N-acetyl]-aminopropionic acid, ethyl ester) and picaridin (1-piperidinecaboxylic acid, 2-[2-hydroxyethyl], 1-methlypropyl ester) at concentrations >15% can repel as well as DEET when applied to skin (315,(322)(323)(324)(325) and are considered effective DEET alternatives. Products containing permethrin should be applied to outer clothing (e.g., shirts and pants) and not directly to skin (314).…”
Section: Box 8 Summary Of Confirmatory Diagnostic Testsmentioning
confidence: 99%
“…Bissinger et al (2009) demonstrated the active ingredient 2-undecanone had a toxic effect against the ticks Amblyomma americanum and Dermacentor variabilis as well as against arthropods (Antonious and Snyder, 2006) and it is therefore formulated in domestic-use insect repellents (Bissinger et al, 2009).…”
Section: Discussionmentioning
confidence: 99%